PENGARUH GENDER, RELIGIUSITAS DAN PRESTASI BELAJAR TERHADAP PERILAKU ETIS AKUNTAN MASA DEPAN (STUDI PADA MAHASISWA AKUNTANSI PERGURUAN TINGGI SWASTA DI WILAYAH DKI JAKARTA) - M. Umar Bakri Hutahahean; Hasnawati Hasnawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
This study discusses the ethical behavior of accountants in the future, in this case is a student majoring in accounting (studies on student private collage in the DKI Jakarta region). The purpose of this study was to examine the influence of gender, religiosity (intrapersonal and interpersonal religiosity) and the academic achievement (GPA) of the ethical behavior of accounting students. Data retrieval is done by distributing questionnaires to 150 students majoring in accounting at The University of Tarumanegara, University of Persada Indonesia YAI, University of Bina Nusantara, and University of Mercu Buana students. The sampling technique used was Convinience Sample and Snowball Sampling. Data quality was tested by using test validity and reliability testing. The analysis tool used is multiple regression test using the F test and T test simultaneous partial. The results of this study indicate that there is no influence of gender on the ethical behavior of accounting students; There is intrapersonal influence of religiosity onethical behavior of accounting students; No interpersonal influence of religiosity onethical behavior of accounting students; There was no effect of academic achievement (GPA) on the ethical behavior of accounting students.